Business Communication. - Rai, Urmila (Global Media, 2009)
UNIT 1BUSINESS LETTERSParts and Layout of a business Letter Essentials of Effective Letter Writing UNIT 2LETTERS RELATED TO ACCOUNTSCollection LettersCorrespondence with Banks Insurance Letters Letters to Public AuthoritiesUNIT 3PURCHASERequests for Quotations and Replies Orders and Replies Complaints Adjustment LettersUNIT 4BUSINESS LETTERSSales Letters Circulars Status Enquiries.